Correlation between triglyceride glucose-waist-to-height ratio and advanced cardiovascular-kidney-metabolic syndrome - Xingxing REN (Zhongguo Linchuang Yixue, 2025)
ObjectiveTo explore the correlation between the triglyceride glucose-waist-to-height ratio (TyG-WHtR) and advanced cardiovascular-kidney-metabolic (CKM) syndrome. MethodsData from the National Health and Nutrition Examination Survey (NHANES) 2007–2018 were used and analyzed, including a total of 14 322 adult participants. The CKM syndrome is classified into 5 stages, with stages 0-2 categorized as the early phase and stages 3-4 as the advanced phase, which were subjected to dichotomous classification analysis. The TyG-WHtR was calculated using triglycerides, glucose, waist circumference, and height. Multivariate logistic regression was used to analyze the correlation between TyG-WHtR and advanced CKM syndrome, adjusting for variables such as age, sex, race, education level, poverty-income ratio (PIR), smoking status, and alcohol consumption. Restricted cubic spline (RCS) analysis was conducted to evaluate the nonlinear relationship between the TyG-WHtR and advanced CKM syndrome. ResultsAmong the 14 322 participants, advanced CKM syndrome accounted for 16.99%. The TyG-WHtR level in the advanced CKM syndrome group was significantly higher than that in the early CKM syndrome group (5.60±0.03 vs 5.02±0.02, P＜0.001). Logistic regression showed that TyG-WHtR was an independent related factor for advanced CKM syndrome (OR＝1.48, 95%CI 1.36-1.61, P＜0.001). Subgroup analyses revealed that the TyG-WHtR was consistently associated with advanced CKM syndrome across different sex, rase, and age groups, with no significant interaction effects observed. RCS analysis revealed a nonlinear positive association between TyG-WHtR and advanced CKM syndrome (Poverall＜0.001, Pnonlinear＝0.014). When the TyG-WHtR exceeded 5, the risk of advanced-stage CKM syndrome showed a significant elevation. ConclusionsThe TyG-WHtR is an independent related factor for advanced CKM syndrome, with a particularly significant risk increase when TyG-WHtR exceeds 5.